Investigation and Analysis of Space Vector Modulation with Matrix Converter Determined Based on Fuzzy C-Means Tuned Modulation Indexs - Ch. Amarendra; K. Harinadh Reddy (Institute of Advanced Engineering and Science, 2016)
Matrix converter performs energy conversion by directly connecting input phases with output phases through bidirectional switches. Conventional power converters make use of bulky reactive elements which are subjected to ageing, reduce the system reliability. The matrix converter (MC) stands as an alternative to conventional power converter. Furthermore MC’s provide bidirectional power flow nearly sinusoidal input and sinusoidal output waveform and controllable input power factor. In this work, three modulation methods have been simulated using MATLAB and compared on the basis of input current harmonics, output voltage harmonics and number of switching per cycle. The three techniques simulated are, Optimal Venturini method, Direct Space Vector Modulation (DSVM) and Indirect Space Vector Modulation (ISVM) on Conventional Matrix Converter (CMC) and obtained form Fuzzy c-Means (FCM). DSVM with FCM is proposed for obtainting best results compared to other three techniques.